Analysis of determinants of infertility among women at in vitro fertilization clinic in Surabaya - Yati Isnaini Safitri; Esty Puji Rahayu; Lailatul Khusnul Rizki; Siska Nurul Abidah; Ima Nadatien (PAGEPress Publications, 2024)
In social life and global health, infertility is common. History of abdominal surgery, body mass index (BMI), endometriosis, menstrual history, and polycystic ovarian syndrome (PCOS) have not been fully explained as female infertility factors. This study examined infertility causes at ASHA in vitro fertilization Primasatya Husada Citra (PHC) Hospital Surabaya. This quantitative study was cross-sectional. In May-July 2023, 82 childbearing-age women with infertility issues visited the hospital and completed questionnaires. Description and analysis were performed using the Wilcoxon rank test to evaluate menstrual history, BMI, PCOS, endometriosis, and abdominal surgery history in relation to infertility. Infertility was statistically associated with abdominal surgery history (P=0.008), BMI (P=0.000), endometriosis diagnosis (P=0.000), and PCOS (P=0.000). Women with abdominal surgery, endometriosis, and PCOS had significant infertility. Women's infertility can be caused by ovulation disorders, tubal and pelvic disorders, or uterine disorders, but one-third of cases are unexplained. Infertility treatment may benefit from addressing abdominal surgery history, BMI, endometriosis, and PCOS. Early intervention and targeted care based on these determinants may improve fertility outcomes and reduce unexplained infertility.